Improving building energy efficiency in India: State-level analysis of building energy efficiency policies - Yu, Sha; Tan, Qing; Evans, Meredydd; Kyle, Page; Vu, Linh; Patel, Pralit L. (Energy policy, 2017)
India is expected to add 40 billion m2 of new buildings till 2050. Buildings are responsible for one third of India's total energy consumption today and building energy use is expected to continue growing driven by rapid income and population growth. The implementation of the Energy Conservation Building Code (ECBC) is one of the measures to improve building energy efficiency. Using the Global Change Assessment Model, this study assesses growth in the buildings sector and impacts of building energy policies in Gujarat, which would help the state adopt ECBC and expand building energy efficiency programs. Without building energy policies, building energy use in Gujarat would grow by 15 times in commercial buildings and 4 times in urban residential buildings between 2010 and 2050. ECBC improves energy efficiency in commercial buildings and could reduce building electricity use in Gujarat by 20% in 2050, compared to the no policy scenario. Having energy codes for both commercial and residential buildings could result in additional 10% savings in electricity use. To achieve these intended savings, it is critical to build capacity and institution for robust code implementation. •We assess state-level impact of building energy policies in India using GCAM.•We link bottom-up and top-down analyses to examine real-world building policies.•Gujarat would experience rapid growth and electrification in building energy use.•Building energy codes can generate significant energy and economic savings by 2050.•A high code compliance rate is critical to achieving intended savings.